Modelling of the ankle joint complex. Reflections with regards to ankle prostheses - Dettwyler, Markus; Stacoff, Alex; Kramers-de Quervain, Inès A.; Stüssi, Edgar (Foot and Ankle Surgery, 2004)
The goal of the present article is to provide a review and summary (2) of biomechanical research on the ankle joint, (3) ankle joint models, (4) ankle endoprostheses, and (5) reflections with respect to possible applications of ankle prosthesis design. Knowledge of the biomechanical function is essential for a successful design of a joint replacement for the ankle, which is highly complex. Presently, predictions of joint compressive forces are the primary basis for the design development of artificial total ankle replacements. Shear forces at the bone-to-implant interface, accountable for an increased loosening rate of the implant, are obviated with the so-called unconstrained design philosophy. However, the knowledge of transverse forces and shank torsional moments in conjunction with artificial ankle replacements and problems possibly related to these loads is rare. This review summarizes contributions of relevance with respect to the modelling of the ankle joints and a prosthetic replacement design and discusses some potentially important aspects for future ankle prostheses.